2011
DOI: 10.20886/jphka.2011.8.3.211-216
|View full text |Cite
|
Sign up to set email alerts
|

Keanekaragaman Epifit Berkayu Pada Hutan Bekas Tebangan Di Hutan Penelitian Malinau (Mrf) – Cifor

Abstract: The aim of this research is to observe the various kinds of wooding epiphytes and its porophyte in the log over forest in the area of 12 hectares in Malinau Research Forest (MRF-CIFOR) Seturan-district of Long Loreh, the regency of Malinau. In that area, it is found nine species with 2,4 individual wooding epphytes at each phorophyte. The Hoya sp., from the family of Asplepidaceae is the most abumdauf wooding epiphytes in the crown and in the bark of the host trees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 1 publication
0
3
0
7
Order By: Relevance
“…Smith et al (2006) stated that the Polypodiales ordo on fern has 15 families, including: Polypodiaceae, Davalliaceae, Oleandraceae, Tectariaceae, Lamariopsidaceae, Dryopteridaceae, Onocleaceae, Blechnaceae, Thelypteridaceae, Woodsiaceae, Aspleniaceae, Dennstaedtiaceae, Saccolomataceae, and Lindsaeaceae. Sujalu (2007) found that there were 88.89% of epiphytic ferns in Malinau Research Forest which were belong to Polypodiales group. Similarly, Supu and Munir (2009) also revealed that as much as 81.82% of ephypitic plant in the forest around Lake Lawulamoni in Kabawo Region were Polypodiales.…”
Section: Introductionmentioning
confidence: 95%
“…Smith et al (2006) stated that the Polypodiales ordo on fern has 15 families, including: Polypodiaceae, Davalliaceae, Oleandraceae, Tectariaceae, Lamariopsidaceae, Dryopteridaceae, Onocleaceae, Blechnaceae, Thelypteridaceae, Woodsiaceae, Aspleniaceae, Dennstaedtiaceae, Saccolomataceae, and Lindsaeaceae. Sujalu (2007) found that there were 88.89% of epiphytic ferns in Malinau Research Forest which were belong to Polypodiales group. Similarly, Supu and Munir (2009) also revealed that as much as 81.82% of ephypitic plant in the forest around Lake Lawulamoni in Kabawo Region were Polypodiales.…”
Section: Introductionmentioning
confidence: 95%
“…Keanekaragaman jenis anggrek epifit yang diperoleh lebih sedikit dibandingkan dengan yang telah dilaporkan di lokasi lainnya. Keanekaragaman jenis anggrek epifit yang telah dilaporkan sebanyak 169 jenis (Siregar, 2008), 30 jenis (Ariyanti dan Pa'i, 2008), 37 jenis (Sujalu, 2008). Jumlah yang hampir sama dilaporkan oleh O'Malley (2009) sebanyak 16 jenis dan 19 jenis (Rikardus et al, 2017), sedangkan Amalia et al (2015), melaporkan dengan jumlah jenis yang lebih sedikit yaitu tujuh jenis anggrek epifit.…”
Section: Pembahasan Keanekaragaman Anggrek Epifitunclassified
“…Tumbuhan epifit kurang mendapat perhatian untuk dikaji secara khusus (Sujalu dan Pulihasih, 2010), namun secara ekologi tumbuhan epifit memiliki habitat berbeda dengan jenis inang tertentu sebagai kesatuan ekosistem suatu kawasan hutan dalam mengatur iklim mikro. Tumbuhan epifit hidup berasosiasi dengan tumbuhan lain (inang) yaitu dengan cara menempel di batang, dahan, dan tajuk pohon, namun tidak bersifat parasitik yang merugikan inang (Sujalu, 2007).…”
Section: Pendahuluanunclassified
“…Tumbuhan epifit hidup berasosiasi dengan tumbuhan lain (inang) yaitu dengan cara menempel di batang, dahan, dan tajuk pohon, namun tidak bersifat parasitik yang merugikan inang (Sujalu, 2007).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation